Literary theory and the claims of history : postmodernism, objectivity, multicultural politics - Mohanty, Satya P. (Satya Prakash), 1954- (Ithaca : Cornell University Press, 1997)
Drawing on detailed analyses of reference, interpretation, and the nature value, Satya P. Mohanty defends a "postpositivist realist" conception of objectivity as a legitimate ideal of all inquiry. He outlines a realist theory of social identity and multicultural politics, showing why radical moral universalism and cultural diversity need to be seen a complementary, rather than competing ideals.
Paul de Man, language, and the politics of meaning -- Reference and the social basis of language -- The limits of Althusser's poststructuralist Marxism -- Jameson's Marxist hermeneutics and the need for an adequate epistemology -- Political criticism and the challenge of otherness -- On situating objective knowledge -- Identity, multiculturalism, justice.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Criticism -- History -- 20th century; Literature, Modern -- 20th century -- History and criticism -- Theory, etc; Postmodernism (Literature); Multiculturalism; Critique -- Histoire -- 20e siècle.; Littérature -- 20e siècle -- Histoire et critique -- Théorie, etc; Postmodernisme (Littérature); Multiculturalisme; multiculturalism; Criticism; Multiculturalism; Postmodernism (Literature); Geschichtsbewusstsein; Literaturtheorie; Literatuurtheorie; Postmodernisme; Culturele verschillen; Objectiviteit; 1900-1999; Criticism, interpretation, etc; History; Electronic books